Γ‐Glu‐Met synthesised using a bacterial glutaminase as a potential inhibitor of dipeptidyl peptidase IV. (8th December 2017) - Yang, Juan; Sun‐Waterhouse, Dongxiao; Cui, Chun; Dong, Keming; Zhao, Mouming
Summary: This study describes γ ‐glutamyl dipeptides as competitive inhibitors of dipeptidyl peptidase‐IV (DPP‐IV), and the feasible synthesis of γ ‐Glu‐Met through transpeptidation catalysed by a commercial glutaminase of Bacillus amyloliquefaciens . γ ‐Glu‐Met, γ ‐Glu‐Leu, γ ‐Glu‐Phe, γ ‐Glu‐Trp or γ ‐Glu‐Tyr exhibited a competitive inhibitory effect on DPP‐IV. The yield of γ ‐Glu‐Met was 26.16% under optimised conditions: 200 mm Gln, 20 mm Met, 0.1 U mL −1 enzyme, pH 9.0, 37 °C and reaction time 3 h. For the first time, the side products containing characteristic sequences, that is poly‐ γ ‐glutamyl short chains with a terminal Met residue ( γ ‐Glu‐ γ ‐Glu‐Met and γ ‐Glu‐ γ ‐Glu‐ γ ‐Glu‐Met) were identified. The superiority of the commercial glutaminase in the synthesis of DPP‐IV‐inhibitory peptides can enable the application of this novel process for manufacturing γ ‐glutamyl‐peptides as potential functional ingredients in the type 2 diabetic diet. Abstract : The γ‐Glu‐Met has been synthesized for its potential inhibitory property for DPP‐4.